2021
DOI: 10.1007/s00705-021-05237-1
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A: a possible host modulator in Chandipura virus infection

Abstract: Chandipura virus (CHPV), belonging to the genus Vesiculovirus of the family Rhabdoviridae, has been identified as one of the causes of pediatric encephalitis in India. Currently, neither vaccines nor therapeutic drugs are available against this agent. Considering that the disease progresses very fast with a high mortality rate, working towards the development of potential therapeutics against it will have a public health impact. Although the use of viral inhibitors as antiviral agents is the most common way to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the current JMV study, 1 the authors showed 70% plaque reduction of CHPV at 20 ug/mL and complete inhibition at 50 and 100 ug/mL of favipiravir in Vero cells. They calculated an EC 50 (concentration at which half of the virus is dead/neutralized) of 92.26 uM, which falls below the predicted cytotoxicity range (CC 50 ) of 4774 uM (750 ug/mL).…”
Section: In Vitro and In Vivo Testing Of The Antiviral Effect Of Favi...mentioning
confidence: 59%
See 4 more Smart Citations
“…In the current JMV study, 1 the authors showed 70% plaque reduction of CHPV at 20 ug/mL and complete inhibition at 50 and 100 ug/mL of favipiravir in Vero cells. They calculated an EC 50 (concentration at which half of the virus is dead/neutralized) of 92.26 uM, which falls below the predicted cytotoxicity range (CC 50 ) of 4774 uM (750 ug/mL).…”
Section: In Vitro and In Vivo Testing Of The Antiviral Effect Of Favi...mentioning
confidence: 59%
“…They calculated an EC 50 (concentration at which half of the virus is dead/neutralized) of 92.26 uM, which falls below the predicted cytotoxicity range (CC 50 ) of 4774 uM (750 ug/mL). 1 The selectivity index, the toxic concentration compared to active concentration of favipiravir against CHPV, was 51.24, which suggests a reasonably good range of concentrations of favipiravir needed to control CHPV infection that would not be toxic to the patients.…”
Section: In Vitro and In Vivo Testing Of The Antiviral Effect Of Favi...mentioning
confidence: 95%
See 3 more Smart Citations